Finite element analysis of combined fracture and delamination on coated substrate under normal and tangential loading - Mohsin, Mohamad Lokman (2018)
Coating systems provide substrate protection from mechanical and thermal failure. Coating is subjected to contact loading of normal and tangential loading, originated from contact pressure and sliding contact. In this thesis, aeroengine brittle material has been modelled to simulate coating failure under combined fracture and delamination failure. Hard brittle coatings modelled are subjected to normal and tangential loads through a finite element (FE) based methodology. A FE model was built by using the ABAQUS FE analysis software. Half cylinder-on flat contact in a two-dimensional model were carried out with mechanical properties of thermal barrier coating and steel/titanium substrate. In this research, changes of three parameters which are coating to substrate elastic mismatch, coating’s thickness and coefficient of friction (COF), were studied to analyse the effect on stress distributions, fracture behaviour and combined fracture and delamination failure. Stress intensity factor (SIF) technique is used to predict unstable crack propagation and cohesive element method (CZM) was developed to predict delamination in the cohesive element layer between coating and substrate. The results show that coating through thickness fracture is dominated by mode I fracture due to tangential stress, S11 experience by the coating. Coating delamination are dominated by mode II fracture associated by shear stress, S12 in the coating interface. Buckling behaviour dominated failure under combined fracture and delamination condition. In general, increasing COF will worsen fracture and delamination failure due to increase of overall stresses. Stiffer coating, will prevent delamination by buckling but will promote coating fracture by increasing tangential stress. It is predicted that, increasing coating thickness will prevent both fracture and delamination due to reduction of stresses and difficulty for buckling.